EVALUASI RADIASI HAMBUR PADA PHANTOM THORAX DENGAN TEKNIK HIGH kV - Putri, Alung Mutiara Hidayatika; Astari, Fisnandya Meita; Mukmin, Amril (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
The high kV technique used in chest radiology aims to minimize the radiation exposure to the patient. However, the use of high kV usually involves a reduction in mAs to decrease the radiation dosage absorbed by the patient. In this case, the photon number decreases with higher kV, resulting in the total scattered radiation not consistently increasing proportionately. This study aims to determine the amount of scattered radiation generated during chest radiography tests utilizing high kilovolt (kV) settings. This research employed a quantitative experimental methodology. The subject of investigation was a thoracic phantom. The utilized exposure factors were 70 kV at 25 mAs, 80 kV at 12.5 mAs, 90 kV at 6.30 mAs, 86 kV at 4 mAs, and 65 kV at 16 mAs. Data analyses were conducted utilizing the Shapiro-Wilk normality test, descriptive statistical methods, and bivariate R regression values. The test findings indicated that the maximum scattered radiation value was recorded at 80 kV and 12.5 mAs, with an average 4.297 mSv. The minimum value was recorded at 86 kV and 4 mAs, totaling 1,458. The coefficient of determination demonstrates a strong relationship between exposure factors and scattered radiation, ranging from 65% to 69%. Increasing kV while decreasing mAs helps reduce scattered radiation. KV 86 and mAs 4 were identified as the most effective parameters for minimizing scattered radiation, making them an optimal selection for high-kV chest radiography, ensuring safety for both the environment and the patient. ABSTRAKTeknik high kV pada pemeriksaan radiologi thorax bertujuan untuk mengurangi dosis radiasi pada pasien, namun penggunaan high kV biasanya disertai dengan penurunan mAs untuk mengurangi dosis radiasi hambur tidak selalu meningkat secara langsung. Penelitian ini dilakukan untuk mengevaluasi besarnya radiasi hambur yang dihasilkan pada pemeriksaan radiologi thorax menggunakan high kV. Penelitian ini menggunakan penilitian kuantitatif dengan pendekatan eksperimen. Objek penelitian berupa phantom thorax. Variasi faktor eksposi yang digunakan adalah 70kV 25 mAs, 80 kV 12,5 mAs, 90 kV 6,30 mAs, 86 kV 4 mAs, dan 65 kV 16 mAs. Hasil pengukuran, data dilakukan uji normalitas sig. Shapiro wilk, uji descriptive statistic dan análisis bivariat uji regresi. Dari hasil pengujian yang dilakukan, telah didapatkan nilai radiasi hambur tertinggi diperoleh pada kV 80 dan mAs 12,5 dengan rata-rata 4,297 mSv, sedangkan nilai terendah pada kV 86 dan mAs 4 yaitu 1,458. Nilai koefisien determinasi menunjukan hubungan kuat antara faktor eksposi dan radiasi hambur sebesar 65%-69%. Peningkatan kV yang disertai penurunan mAs dapat menurunkan radiasi hambur. Pada kV 86 dan mAs 4 dinilai paling efektif menghasilkan nilai radiasi hambur yang rendah, sehingga dapat menjadi pilihan optimal untuk penerapan pemeriksaan radiografi thorax  dengan tekni high kV yang aman bagi lingkungan dan pasien.